2014
DOI: 10.1186/bf03351638
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of multidisciplinary observations before, during and after the Kocaeli (Izmit) earthquake in the western part of the North Anatolian Fault Zone

Abstract: On August 17, 1999, a destructive earthquake occurred in the western part of the North Anatolian Fault Zone, Turkey. The earthquake source region has been designated as a seismic gap and an M7-class earthquake has been supposed to occur someday in the future so as to fill this seismic gap. So far we have undertaken various kinds of observations in this area and we could obtain some valuable data before, during and after the mainshock. Here we report some of the preliminary results of our recent studies, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 27 publications
7
70
0
Order By: Relevance
“…These features are consistent with the observations using magnetotelluric equipment at locations close to other major earthquakes (Chen and Chen, 2000;Honkura et al, 2000). Rock susceptibilities change with accumulating stress (Stacey, 1962;Nagata, 1970) during the pre-earthquake period.…”
Section: Discussionsupporting
confidence: 79%
“…These features are consistent with the observations using magnetotelluric equipment at locations close to other major earthquakes (Chen and Chen, 2000;Honkura et al, 2000). Rock susceptibilities change with accumulating stress (Stacey, 1962;Nagata, 1970) during the pre-earthquake period.…”
Section: Discussionsupporting
confidence: 79%
“…Honkura et al (2000) and Oshiman et al (2002) made similar MT surveys and showed the preliminary results as twodimensional Earth models. Tank et al (2003) then imaged the western part of the epicentral region of theİzmit earthquake, in order to study the electrical resistivity structure with respect to the characteristic seismic behavior.…”
Section: Audio Frequency Magnetotellurics (Amt) Data Collectionmentioning
confidence: 83%
“…Pride and Morgan, 1991;Gershenzon, 1992;Pride, 1994;Pride and Haartsen, 1996;Haartsen and Pride, 1997;Garambois and Dietrich, 2002;Huang, 2002;Ren et al, 2010a, b). Appearance of unambiguous electric field changes was mostly synchronized with the arrival of seismic wave (Yamada and Murakami, 1982;Honkura et al, 2000Mogi et al, 2000;Nagao et al, 2000;Matsushima et al, 2002;Ujihara et al, 2004). Recently we proposed a new mechanism for electric field generation by seismic wave or more specifically by ground motion, based on some observational examples (Honkura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%